Democratisation in the Middle East : dilemmas and perspectives - Rahbek, Birgitte, 1944- (Aarhus University Press, 2005)
The main aim of the book is to provide a forum for opinions held by Arabs who are neither Western puppets nor fanatical nationalists or Islamists, but rather academics with a vast knowledge of the Middle East as well as of the West.